Custom triflange acetabular components for large acetabular defect reconstruction in revision total hip arthroplasty: a systematic review and meta-analysis on 1218 patients - Demien Broekhuis; Rutger Tordoir; Zoe Vallinga; Jan Schoones; Bart Pijls; Rob Nelissen (EFORT Open Reviews, 2023)
Purpose: This is a systematic review and meta(regression) analysis to assess the performance of custom triflange acetabular components (CTAC) in total hip arthroplasty (THA) revision surgery. Implant-related complications, failure rate, functional outcomes and implant and surgical technique-related predictors for outcome were assessed. Methods: This systematic review was performed according to PRISMA guidelines and registered with PROSPERO (2020 CRD42020209700). PubMed, Embase, Web of Science, COCHRANE Library and Emcare were searched. Studies on Paprosky type 3A and 3B or AAOS type 3 and 4 acetabular defects with a minimum follow-up of 12 months and cohorts > 10 patients were included. Results: Thirty-three studies were eligible for inclusion (n = 1235 hips, 1218 patients). The methodological quality of the studies was moderate (AQUILA: 7.4/11 points). Considerable heterogeneity was observed in terms of complications, re-operations and implant failure reporting. The total incidence of implant-related complications was 24%. The incidence of re-operation for any reason was 15%, and the implant failure rate was 12% at a mean of 46.9 months and the post-operative Harris Hip Score improved by a mean of 40 points. Several predictors for outcome were found, such as implant generation, follow-up length and study start date. Conclusions: The use of CTAC in revision THA has satisfactory complication and implant failure rates. The CTAC technique improves post-operative clinical outcomes and the meta-regression analysis showed that there is a clear association between improvements in the CTAC performance and the evolvement of this technique over time.